SOLID WASTE AND NO INFRINGEMENT OF ENVIRONMENTAL LAW: a study in the municipality of Garanhuns-PE - França, Elaynne Mirele Sabino de; Chaves, Ana Maria Severo; Costa, Samuel Othon de Souza (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The present work conducts a study on the viability of Law 12,305 that deal with on solid wast (RS), havenig as one of this measure main the deactivation of local environmental conditions unsuitable to receive and adopt the RS sanitary landfills indicated as possibility to dispose of suitable. We seek show considerations about the concept of sustainable environmental conditions environmental deposits of solid waste and the management of the actions and municipal management. was performed of start considerations of concepts that treat of the theme in the literature and practice in loco to survey of photographic records and a pretended diagnosis of the study area. With this can identify which practices are adopted and as environmental legislation PNRS (national solid waste policy) in invigorating being applied. Was performed an outline of the situation of the sanitary landfill located in the municipality of Garanhuns in Wasteland state of Pernambuco. One can observe management and environmental risks posed by the some sanitary landfill and risk of unhealthiness to the acting workers in the area as well as the legal determination for deactivation and construction of sanitary landfills. We pointed if we had more cooperative recycling of waste, this would entail the decrease of part of the of the RS "dumps" and landfills, decreasing the impacts on the environment.